(untitled) (Al-Mansour Journal, 2022)
The study is to define the concept of civil and commercial capacity through identifying the concept and persons who have the necessary capacity to do business. The study then tries to discriminate between the natural person and the legal entity, comparing these with civil legislations and Iraqi and Arab legislations. The ultimate aim is to attain stability and to form a unified stand in the sense that every person whether natural or legal can start commercial works. Eventually he or she acquires the status of a merchant in accordance with conditions delimited by commercial legislations. The paper focally revolves round the eligibility of the natural person only, with a fleeting reference to the capacity of the legal person. The scheme of this research falls into three thematic divisions. The first division is concerned with the concept of commercial capacity, the second with natural individuals who enjoy the necessary capacity to do commercial work. The thematic strand consists of four demands. The first concerns the capacity of the adult, the second, the capacity of non- adults, the third the capacity of a married woman, the fourth the capacity of the foreign individual. The third thematic strand is to discriminate between the natural person and the legal one. The paper ends with a conclusion.